2022
DOI: 10.1016/j.heliyon.2022.e08717
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between benign paroxysmal positional vertigo (BPPV) and sleep quality

Abstract: Background: Benign paroxysmal positional vertigo (BPPV) is a common cause of vertigo precipitated mainly by changes in head position for example during sleep. The relationship between sleep quality and BPPV has not been studied sufficiently. We decided to compare sleep quality between posterior canal BPPV patients and controls. Methods: A total of 120 patients with posterior canal BPPV and 120 controls without BPPV were included. Demographic data as well as body mass index (BMI), cigarette smoking and medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…A large population-based study found that sleep duration per night was either significantly shortened or very prolonged in persons with vestibular vertigo [ 16 ]. Also, looking at specific vestibular pathologies, patients with benign paroxysmal positional vertigo (BPPV) [ 17 ] or vestibular migraine [ 18 ] reported significantly worse sleep quality than healthy controls. This detrimental effect on sleep was even more pronounced in patients with a longer history of BPPV [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A large population-based study found that sleep duration per night was either significantly shortened or very prolonged in persons with vestibular vertigo [ 16 ]. Also, looking at specific vestibular pathologies, patients with benign paroxysmal positional vertigo (BPPV) [ 17 ] or vestibular migraine [ 18 ] reported significantly worse sleep quality than healthy controls. This detrimental effect on sleep was even more pronounced in patients with a longer history of BPPV [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Also, looking at specific vestibular pathologies, patients with benign paroxysmal positional vertigo (BPPV) [ 17 ] or vestibular migraine [ 18 ] reported significantly worse sleep quality than healthy controls. This detrimental effect on sleep was even more pronounced in patients with a longer history of BPPV [ 17 ]. Moreover, these combined findings lead to the hypothesis that chronic or long-term vestibular disorders such as unilateral vestibular hypofunction have an even greater negative impact on sleep quality than acute vestibular problems [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported that the incidence of sleep disorders in patients with BPPV uctuates between 35% and 60% [21,22] . This uctuation could be related to the included population and the accuracy of the scale evaluation.…”
Section: Discussionmentioning
confidence: 99%
“…BPPV-related dizziness and imbalance can also result in social withdrawal and isolation due to concerns about experiencing vertigo in public settings [10,11]. Sleep disturbances are common, as positional changes in bed can trigger vertigo episodes, affecting the overall quality of rest and contributing to fatigue and irritability during the day [10][11][12]. The impact of BPPV on mental health should not be overlooked, as chronic dizziness and the associated limitations can lead to depression and decreased overall well-being [13].…”
Section: Bppv and Quality Of Lifementioning
confidence: 99%